Development of Prezzi Media in Landslide Disaster Mitigation Learning in Indonesia (Case Study at SMA Xavarius in Bukittinggi) - Ramadhani, Tiara Suci (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research and development was to develop Prezi presentation media in the learning of landslide disaster mitigation that was feasible to be used in the learning process and to know the effectiveness of media at class X SMA Xavarius in Bukittinggi. This research model used to research and development based on Borg and Gall (1983) development model. The steps used include: 1) initial needs analysis, 2) product development, 3) expert validation, 4) product revision I, 5) field trials, 6) product revisions II, and 7) final product. The result of this research shows that Prezi media in learning landslide disaster mitigation was valid / proper to be used, proved by scoring by media expert 96,84% (valid/worth using); material experts of 89.00% (valid / worth using); student trial test score of 89.53% (valid / worth using); and teacher user experiments of 86.89% (valid / worth using). Suggested of this research for subsequent development are developing Prezi media with other materials and using the 2013 curriculum